Integration of Islamic Values In Growing Human Rights Awareness Attitude To The Challenges of The Digital World - Ari Ustoyo, Valensiana Vortunata; Lailiyah, Nila Ni’matul; Khasanah, Iswatul (Jurnal Pendidikan Ilmu Sosial, 2021)
In civic education, one of the materials is about human right. It introduces the students to know what students’ rights since in the childhood in living as a citizen who has ideology Pancasila. Islamic human right perspective also needs to be taught. This study aimed to explain integrating Islamic values in teaching human right in digital era. A literature study was used in this study. The integration of Islamic value in teaching human right is intended to students has Pancasila human right insight is the study result. The are some efforts for teacher to do in raising students right’ awareness as religious people by cultivating Islamic values in teaching human rights which intended to establishing students’ attitude and behavior .It is in order to the students are able to face the challenges of digital era such as; human rights violations, cyber-crimes, radicalism contents, etc.